2022
DOI: 10.1097/md.0000000000030185
|View full text |Cite
|
Sign up to set email alerts
|

Health vulnerabilities in female sex workers in Brazil, 2016

Abstract: Female sex workers (FSW) suffer stigma and discrimination that negatively impact their physical and mental health and affect access to health care services. This paper aims to describe selected health indicators among FSW in 12 Brazilian cities in 2016. Brazilian cross-sectional Biological Behavioral Surveillance Survey was conducted in 2016 among 4328 FSW recruited by respondent-driven sampling. The sample weighing was inversely proportional to participant's network sizes and the seeds were excluded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The finding of conceiving after entering sex work is consistent with studies done among the same population of FSWs where it was reported they conceived during sex work (Beckham et al, 2015;Du Plessis et al, 2020;Moore et al, 2023;Shewale & Sahay, 2022). The findings were also consistent with a study in Brazil, which documented that most FSWs started prenatal care in the first trimester of their pregnancy, with antenatal coverage at 85.8% (Braga et al, 2022).…”
Section: Demographic Datasupporting
confidence: 90%
“…The finding of conceiving after entering sex work is consistent with studies done among the same population of FSWs where it was reported they conceived during sex work (Beckham et al, 2015;Du Plessis et al, 2020;Moore et al, 2023;Shewale & Sahay, 2022). The findings were also consistent with a study in Brazil, which documented that most FSWs started prenatal care in the first trimester of their pregnancy, with antenatal coverage at 85.8% (Braga et al, 2022).…”
Section: Demographic Datasupporting
confidence: 90%
“…During full-text reviews, seven publications were determined to have used the same datasets produced from three studies to report on similar outcomes. [37][38][39][40][41][42][43] These records were merged to represent the three studies and results from one publication per study were extracted for this review. In total, 18 peer-reviewed publications were included in this review.…”
Section: Search Resultsmentioning
confidence: 99%
“…This qualitative study based in Mumbai, India, reported that few FSWs discussed receiving breastfeeding counseling from medical providers during in-depth interviews. 43 In addition, among FSWs that did report counseling experience, they described the guidance they received as primarily focused on discouraging breastfeeding. This was due to providers’ concerns about mother-to-child transmission of HIV and women’s ability to maintain an adequate milk supply.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the global community has failed to sufficiently and proactively identify, and respond to secondary impacts that intensify as "globally networked hyperrisks" [40] generated by "strongly connected, global networks" and complex, interacting, "highly interdependent systems", cascading across various sectors and scales-local, regional, national and international, individual, community/population, public, and global [39][40][41]. In addition, existing risk management and governance infrastructure for disease and disease outbreak policies often lack adequate mechanisms for considering the diverse needs of vulnerable or at-risk populations, including those living in informal settlements and geographically isolated settings [42], socio-economically deprived or underserved populations [43,44], those who are homeless [45], racialized visible minorities [46,47], women [48], the elderly [49], persons with disabilities [50], Indigenous communities [51], informal workers [52], migrants and refugees [53], those without citizenship rights [54,55], sex workers [56][57][58], and the two-spirit, lesbian, gay, bisexual, transgender/transsexual, queer, intersex, asexual, polysexual/pansexual (2SLGBTQIAP+) community [59], among others.…”
Section: Public Healthmentioning
confidence: 99%